Impact of COVID-19 Outbreak on the Gynecological Outpatients HPV Infection Rate in Wuhan, China: A Retrospective Observational Study - Liu, Hang; Yao, Qian; Li, Di; Zhao, Zhiming; Li, Yan (Frontiers in Medicine, 2022)
Background The recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has caused millions of deaths and greatly influenced the timely diagnosis and treatment of other diseases. Throughout the pandemic, there was a dramatic reduction in the prevalence of several sexually transmitted infections. However, the impact of the ongoing pandemic on human papillomavirus (HPV) infection rates has not been investigated thus far. Materials and Methods We retrospectively collected data regarding HPV and cervical cancer screening results of outpatients from gynecological clinics of a tertiary hospital from 1 December 2018 to 31 December 2020 in Wuhan. Based on the timeline of the SARS-CoV-2 pandemic in Wuhan, we divided this period into four relatively independent stages to compare the HPV screening visit numbers and infection rates. Results There was a 50% drop in HPV screening visits and a 10% drop in HPV infection rates throughout the pandemic when compared with the numbers collected before the pandemic. Strict lockdown measures greatly decreased the HPV infection rate (17.03 vs. 8.29, P = 0.003). During the pandemic, the most prevalent HPV genotypes were HPV 16, 52, 58, and 53. After the pandemic, the HPV infection rate recovered quickly, but it was still slightly lower than the infection rate found before the outbreak (23.3 vs. 21.2%). Conclusion During coronavirus disease 2019 (COVID-19) pandemic, cervical cancer screening visits and HPV infection rates have decreased dramatically. The HPV transmission has also decreased after strict lockdown. Effective HPV and cervical cancer screening programs should be strengthened immediately to reduce the transmission of HPV during and after the pandemic.